2014
DOI: 10.1016/j.chembiol.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Quorum-Sensing Receptor LasR Reveals Interactions that Govern Activation and Inhibition by Nonlactone Ligands

Abstract: SUMMARY Gram-negative bacteria use N-acyl L-homoserine lactone (AHL) quorum sensing (QS) signals to regulate the expression of myriad phenotypes. Non-native AHL analogs can strongly attenuate QS receptor activity and thereby QS signaling; however, we currently lack a molecular understanding of the mechanisms by which most of these compounds elicit their agonistic or antagonistic profiles. In this study, we investigated the origins of striking activity profile switches (i.e., receptor activator to inhibitor, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 50 publications
7
61
0
Order By: Relevance
“…2D). Our results join previous findings suggesting that autoinducer acyl side chain length is particularly important in dictating the stimulation of LasR activity (36) and recent work cataloging hydrogen-bonding interactions in the LasR LBD critical for LasR activation and inhibition (37,38).…”
Section: Impact Of Oxidative Stress On the Lasr Ligand Binding Domainsupporting
confidence: 89%
“…2D). Our results join previous findings suggesting that autoinducer acyl side chain length is particularly important in dictating the stimulation of LasR activity (36) and recent work cataloging hydrogen-bonding interactions in the LasR LBD critical for LasR activation and inhibition (37,38).…”
Section: Impact Of Oxidative Stress On the Lasr Ligand Binding Domainsupporting
confidence: 89%
“…[39][40][41][42][43][44] Both Suga and Blackwell have shown that this residue determines whether a ligand acts as an agonist or antagonist. 45,46 Ligands that exhibit unfavorable interactions with Trp60 have antagonistic profiles. Recently Blackwell also revealed that the interactions between a ligand and Tyr56 and Ser129 in LasR are also important in determining whether a ligand acts as an antagonist or agonist since these residues bond to the carbonyl of the 3-oxo-C12-HSL ligand to position the lactone head group towards Tyr 60, which is a key residue.…”
Section: Resultsmentioning
confidence: 99%
“…Recently Blackwell also revealed that the interactions between a ligand and Tyr56 and Ser129 in LasR are also important in determining whether a ligand acts as an antagonist or agonist since these residues bond to the carbonyl of the 3-oxo-C12-HSL ligand to position the lactone head group towards Tyr 60, which is a key residue. 45,47 Docking experiments [48][49][50] revealed that the docked poses of 3-oxo-C12-HSL and of the 3-aminooxazolidinone analog (1) are similar, with the exception of the orientation of the 3-oxo group (see Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that targeting LasR may have the largest impact on QS-related virulence in P. aeruginosa (Galloway et al, 2012), since LasR activation directly upregulates certain virulence phenotypes (e.g., proteases, biofilm) and indirectly upregulates other virulence phenotypes (e.g., pyocyanin, rhamnolipid) through positive regulation of both the RhlR and PqsR systems (Asfahl and Schuster, 2018; Welsh and Blackwell, 2016a, b). Therefore, considerable efforts have been directed toward designing molecules to antagonize LasR and thereby block its associated virulence phenotypes, with notable contributions from the Bassler (O’Loughlin et al, 2013), Blackwell (Gerdt et al, 2014; Geske et al, 2007; Moore et al, 2015; O’Reilly and Blackwell, 2016), Greenberg (Muh et al, 2006; Müh et al, 2006), Meijler (Amara et al, 2011; Amara et al, 2009), Spring (Galloway et al, 2011; Hodgkinson et al, 2012), and Suga (Smith et al, 2003a; Smith et al, 2003b) laboratories.…”
Section: Introductionmentioning
confidence: 99%